2014
DOI: 10.1111/mms.12196
|View full text |Cite
|
Sign up to set email alerts
|

Song sharing and diversity in the Bering‐Chukchi‐Beaufort population of bowhead whales (Balaena mysticetus), spring 2011

Abstract: Bowhead whales (Balaena mysticetus) of the Bering‐Chukchi‐Beaufort population migrate in nearshore leads through the Chukchi Sea each spring to summering grounds in the Beaufort Sea. As part of a population abundance study, hydrophones were deployed in the Chukchi Sea off Point Barrow, (12 April to 27 May 2011) and in the Beaufort Sea (12 April to 30 June 2011). Data from these sites were analyzed for the presence of bowhead whale song. We identified 12 unique song types sung by at least 32 individuals during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…It is not known whether individual bowhead whales sing multiple song types in a season, but some are known to share the same song type in the same period in the Bering–Chukchi–Beaufort (BCB) population [ 14 , 16 ]. Nor is it known if individual bowhead whales maintain the same song throughout their lifetime or if they switch within and/or between years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known whether individual bowhead whales sing multiple song types in a season, but some are known to share the same song type in the same period in the Bering–Chukchi–Beaufort (BCB) population [ 14 , 16 ]. Nor is it known if individual bowhead whales maintain the same song throughout their lifetime or if they switch within and/or between years.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study from the Fram Strait in 2008–2009 provided the first indication that tens of song types were produced by bowhead whales in this region within a single overwinter period [ 8 ]. No year-round studies of song diversity exist for other bowhead whale populations although multiple song types in a single year have been documented for two other populations [ 15 , 16 ]. Herein, we document extremely high inter- and intra-annual diversity in the mammalian song from the Spitsbergen bowhead whale population.…”
Section: Introductionmentioning
confidence: 99%
“…Calls were described as ''simple'' (frequency-modulated, FM) or ''complex'' (amplitude-modulated, AM) signals, with repetitive call sequences (''simple songs'') identified in a single springtime recording. These and later recording efforts over the last 30 years have further advanced understanding of the bowhead's remarkable suite of acoustic behaviors including broadband impulses (referred to as gunshot calls, Würsig and Clark, 1993) and complex song compositions consisting of two-voiced, patterned sequences lasting about a minute (Clark and Johnson, 1984;Würsig and Clark, 1993;Delarue et al, 2009;Stafford et al, 2008Stafford et al, , 2012Tervo et al, 2009;Johnson et al, 2014). Most bowhead sounds are distinctly different from sounds produced by other marine mammals endemic to the sub-arctic and arctic habitats.…”
Section: Introductionmentioning
confidence: 98%
“…Bowhead whale songs have been described following the same hierarchical framework established to study humpback whales, with sequences of repeated units composing phrases, phrases composing themes, and themes composing a song 1 . Contrarily to humpback whales that share song within the same population, bowhead whales appear to share songs within a limited cluster of animals 5 , 8 . In the first review of the earliest acoustic researches on bowhead whales Würsig and Clark 1 described a ‘great deal of intra and inter individual song variation’ and the following studies have consistently reported song variability.…”
Section: Introductionmentioning
confidence: 99%
“…Manual or automated categorisation into unit types can be furthermore complicated by the graded nature of the bowhead whale repertoire. For example, Johnson et al 8 described ‘subnotes’ (subtypes of units) along a graded unit sequence (similar to gradual changes in units described in humpback whale shifting themes 18 , 19 ), where both unit duration and frequency parameters evolved along the song. The authors eventually assigned the last units of the sequence to a different type, based on “trend of frequency”, a criterion that has not been reported in other song studies.…”
Section: Introductionmentioning
confidence: 99%